2017
DOI: 10.1016/s2352-3026(17)30012-1
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag versus placebo for low-risk myelodysplastic syndromes with thrombocytopenia (EQoL-MDS): phase 1 results of a single-blind, randomised, controlled, phase 2 superiority trial

Abstract: Associazione QOL-ONE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 28 publications
(47 reference statements)
11
118
2
3
Order By: Relevance
“…In a subsequent randomised phase II study versus placebo in LR‐MDS with thrombocytopenia, romiplostim reduced the incidence of severe bleeding and platelet transfusions, but there was a suspected increase in the AML risk that was not confirmed with longer term follow‐up (Kantarjian et al , ). Eltrombopag also produces a platelet response in about 50% of patients, with no apparent increase in the risk of disease progression (Oliva et al , ), including with longer follow‐up (Oliva et al , ). However, long term follow‐up may be lacking in some studies, and the number of reported patients treated with eltrombopag, in particular, remains limited.…”
Section: How We Treat Lower‐risk(lr) Mdsmentioning
confidence: 99%
“…In a subsequent randomised phase II study versus placebo in LR‐MDS with thrombocytopenia, romiplostim reduced the incidence of severe bleeding and platelet transfusions, but there was a suspected increase in the AML risk that was not confirmed with longer term follow‐up (Kantarjian et al , ). Eltrombopag also produces a platelet response in about 50% of patients, with no apparent increase in the risk of disease progression (Oliva et al , ), including with longer follow‐up (Oliva et al , ). However, long term follow‐up may be lacking in some studies, and the number of reported patients treated with eltrombopag, in particular, remains limited.…”
Section: How We Treat Lower‐risk(lr) Mdsmentioning
confidence: 99%
“…A number of studies are evaluating eltrombopag in MDS, another TPO agonist. Results from the phase 1 single‐arm, randomized portion of the phase 2 superiority EQoL‐MDS study evaluating the efficacy and safety of eltrombopag in patients with lower‐risk MDS where recently published and reported significantly higher platelet responses (47% versus 3%, P = .0017) and fewer bleeding events (14% versus 42%, P = .0025) in the eltrombopag arm compared to placebo. No differences in leukemic transformation where observed (12% versus 16%, P = .81).…”
Section: Risk Adapted Therapymentioning
confidence: 99%
“…largely reversible [55]. In contrast, clinical studies in patients with either low-risk or high-risk MDS did not show an increased risk of disease progression in those receiving eltrombopag monotherapy as compared with those receiving placebo [56][57][58]. However, an apparent increase in AML progression rate was noted in patients with high-risk MDS who were treated with eltrombopag in combination with azacytidine versus patients who received azacytidine alone (18% versus 11%, respectively) [59].…”
Section: Megakaryocyte Maturation and Proplatelet Formationmentioning
confidence: 99%